Structure, Dielectric Properties and AC Behavior of Commercial Polytetrafluroethylene (PTFE) Polymer - Shujahadeen B. Aziz; Hameed M. Ahmed (ARO-The Scientific Journal of Koya University, 2016)
In this work the relative permittivity (ε''), dielectric loss (ε'') and AC-conductivity for commercial polytetrafluroethylene (PTFE) have been measured at different temperatures (20-110°С) and over the frequency range from 10 KHz to 1 MHz. The infrared (IR) spectra of PTFE also been investigated to detect the presence of polar groups and carbon double bonds. The relative permittivity had observed to decrease with increasing frequency and temperature. Some loss peaks were observed in the dielectric loss spectra, which referred to the relaxation, arises from the orientation of unsaturated double (C=C) bond and polar additives. The diameter of the semicircles in Cole-Cole (ε' versus ε'') plots are not coincides with x-axis at different temperature which reveals that the relaxation processes are non-Debye type. The AC-conductivity increases with increasing of frequency and almost independent on the temperature.